Resection of Ulnar Nerve Giant Cell Neurinoma - Tjokorda Gde Bagus Mahadewa (Indoscholar, 2018)
Giant cellular ulnar nerve neurinoma is a very rare condition. According to the literature, the author reports the first case while only two other reports of the cellular neurinoma can be found in English literature in different locations. The author presents the case of large size cellular neurinoma of the ulnar nerve, where the primary tumour was resected using the shelled out technique, without neurolysis and any nerve repair. Histopathologic characteristics, radiological findings and clinical data on these tumours were reviewed, and the proposed chosen surgical technique, which differs from that used in the previous cases and taking into account the rate of recurrence after total resection.